Фольклорно-етнографічна діяльність Бориса Грінченка - Хомутенко, А. (Народна творчість та етнографія, 2005)
Boris Hrynchenko is a cultural activist of the end of the 19th- beginning of the 20th Century, who began his public work at the time when there were not many conscious cultural Ukrainian movements. He early in his life realized the importance of the folklore recordings. His folklore oriented attitude he expressed ion articles, letter, reviews. He was colleting, publishing and editing folk anthologies through his entire life. This article gives a lot of information about B. Hrynchenko as a field worker and collector of folk materials, describes his principles and understanding of the work done with folk materials collected by him or which have been send to him for publishing, as well as some interesting biographical facts.